2021
DOI: 10.1111/bjc.12280
|View full text |Cite
|
Sign up to set email alerts
|

Investigating associations between hoarding symptoms and affective and cognitive empathy

Abstract: Objectives. Hoarding is associated with poor interpersonal functioning, such as social isolation and difficulties in forming relationships, but the reasons for these social problems are not well understood. Previous studies have identified empathy as an important precursor to social functioning, particularly for clinical disorders characterized by social deficits. The aim of the current study was therefore to investigate associations between measures of cognitive and emotional empathy and hoarding symptoms.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Further, another study revealed that the studied older adults with compulsive hoarding problems have an average age of beginning and development of hoarding symptoms of 67.5, ranging from 60-87 (American Psychiatric Association, 2013; Dozier et al, 2016). The act of acquisition among older adults with hoarding behaviors gives them a sense of reassurance, productivity, and more self-control (Chen et al, 2021). Their possessed items helped them feel more connected to others as well as their personal history.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, another study revealed that the studied older adults with compulsive hoarding problems have an average age of beginning and development of hoarding symptoms of 67.5, ranging from 60-87 (American Psychiatric Association, 2013; Dozier et al, 2016). The act of acquisition among older adults with hoarding behaviors gives them a sense of reassurance, productivity, and more self-control (Chen et al, 2021). Their possessed items helped them feel more connected to others as well as their personal history.…”
Section: Introductionmentioning
confidence: 99%
“…Choi et al (2015) found that marital status, number of friends, frequency of social interactions, and many personal roles have long been shown to protect well-being, boost self-esteem, and reduce anxiety and depressive symptoms. The investigation of interpersonal relationships in the context of hoarding behaviors among aged people revealed that clutter noticeably affects the continuity of these relationships (Chen, et al, 2021). It was reported that older adults with hoarding behaviors tend to have diverse beliefs, memories, emotional attachment, control, and responsibility concerning their possessions, which marginally leads to interpersonal problems (Chen, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation